USING OF METHODS OF IMPULSE INFLUENCE IN FOUNDRY - A. A. Andrushevich; I. N. Kazanevskaja; M. N. Churik (Литьë и металлургия)
Using of pulse processing of different intensity for production of high-grade castings and details of aluminium alloys, including of secondary aluminium waste and scrap, is possible on the basis of application of complex technology of foundry-metallurgical redistribution and provides achievement of increased physical and mechanical and required exploitation characteristics.